Multiscale structured germanium nanoripples as templates for bioactive surfaces. Issue 15 (30th January 2017) - Dell'Anna, Rossana; Masciullo, Cecilia; Iacob, Erica; Barozzi, Mario; Giubertoni, Damiano; Böttger, Roman; Cecchini, Marco; Pepponi, Giancarlo
Abstract : A novel two-step transfer process, that produces by nanoimprinting lithography biocompatible polymeric nanowired ripples, starting from germanium surfaces nanopatterned by irradiating gold ions. Abstract : Nanostructured germanium substrates are produced by gold ion implantation; they show periodic ripples of nanometer size, decorated on the top and partially on one side with a forest of curled nanowires that end with gold-rich nanoparticles. For the first time, through a novel two-step soft lithography transfer process, the multi-scale nanopatterns are replicated, with features well below 100 nm, on biocompatible 2-norbornene ethylene cyclic olefin copolymer substrates. Given the suitable aspect ratio of the nanoripples and the peculiarity of their multiscale structure, the final substrates are available for cell–material interaction studies that can shed light on the role of the hierarchy of nanostructured materials in controlling the large-scale cellular behavior on biocompatible scaffolds. This work also presents an original combination of numerical analyses of scanning force microscopy images, which allows an accurate quantitative description of the outputs of the two-step transfer process.